Traffic theory and the Internet. - Roberts, J.W (IEEE Communications magazine)
We argue that traffic theory, an essential component in the design of traditional telecommunications networks, should be increasingly applied in the development of the multiservice Internet. We discuss the statistical characteristics of Internet traffic at different time scales. Modeling is facilitated on identifying the notion of flow and distinguishing the categories of streaming and elastic traffic. We review mathematical modeling approaches useful for predicting the relationship between demand, capacity and performance for both streaming and elastic flows. Derived results indicate the limitations of service differentiation as a means for guaranteeing QoS and highlight the importance of traditional traffic engineering approaches in ensuring that the network has sufficient capacity to handle offered demand